INFLUENCE OF MANURE AND FERTILIZERS ON SOME CHEMICAL AND BIOLOGICAL PROPERTIES OF SOIL Am> WATER OF A BRACKISHWATER FISH POND - Chattopadhyay, G N; Mandal, L N (Indian Journal of Fisheries, 2011)
The change* in chemical and biological properties of soil and water of a brackishwater flish pond for one year, effected by a combined application of cowdung, urea and single super phosphate, showed that the behaviour of different nutrient elements in water and soil phase of the pond is largely influenced by prevailing water salinity levels. Rapid disappearance of the added nutrients from available forms suggested that the fertilization period in such ponds should be made short. Application of manure and fertilizers was found to be effective in increasing the production of plankton and especially soil flora. Adverse effects of manuring with raw cowdung on the growth of bottom fauna indicated that use of composted manures might be more beneficial for such ponds.